Acupressure only as pain relief for patient with multiple drug allergies undergoing oocyte retrieval - Abdul Hamid, Habibah; Mustafa, Kamarul Bahyah; Denegama, Padmamuni Ariyatilak; Abdul Karim, Abdul Kadir; Omar, Mohamad Hashim; Rashid, M. Razi Zainul (Elsevier Ltd, 2016)
In vitro fertilization (IVF) is associated with significant stress, which can affect the general wellbeing of the couple as well as the outcome of treatment. Oocyte retrieval (OR) is the fundamental step in the IVF/intracytoplasmic sperm injection (ICSI) cycle. Transvaginal ultrasound-guided OR (TVOR) is the most common method used in assisted reproductive technology (ART). However, even though TVOR is a short and minimally invasive procedure, it is stressful and undoubtedly painful [1]. Such pain is due to the passage of a double-bore needle through the vaginal wall and ovarian capsule followed by mechanical stimulation within the ovary during the procedure.